ЯЗЫКОВОЕ ПРОВИДЕНИЕ П.А. ФЛОРЕНСКОГО Лариса М. (Philological Studies, 2019)
In the article an attempt is made to interpret linguistic views of a well-known Russian philosopher, mathematician, theologian and linguist, whose ideas were not demanded by the society he lived in. Florenski’s most famous linguistic views are presented views are presented in his works: “Antinomies of language” (1918), “Magic of the word” (1920), “The structure of the word” (1922), “The Term” (1917-1922), “The names” (1926), “Symbolarium”. Florenski regarded a complex nature of the word. He argued the reader into accepting the fact that a narrow view of the word could mislead linguists about the real nature of the word. Florenski also regarded the term, as a special mental technical formula that lied in its basement. Florenski’s linguistic theory has made a definite contribution into linguistics of the beginning of the XXth century. It is quite evident that his views have made an impact on modern linguistics as well.